2013
DOI: 10.1016/j.bbadis.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of kidney and protective effects of grape seed procyanidin B2 in db/db mice indicate MFG-E8 as a key molecule in the development of diabetic nephropathy

Abstract: Diabetic nephropathy, as a severe microvascular complication of diabetic mellitus, has become the leading cause of end-stage renal diseases. However, no effective therapeutic strategy has been developed to prevent renal damage progression to end stage renal disease. Hence, the present study evaluated the protective effects of grape seed procyanidin B2 (GSPB2) and explored its molecular targets underlying diabetic nephropathy by a comprehensive quantitative proteomic analysis in db/db mice. Here, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 55 publications
4
35
0
Order By: Relevance
“…These secondary metabolites, especially flavonoids, play multiple roles in grape and attract more and more attentions due to their health benefits (Anastasiadi et al, 2010; Kim et al, 2013; Zhang et al, 2013). During grape berry development, the detected flavonoids presented two distinct changing patterns (Figure 2E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These secondary metabolites, especially flavonoids, play multiple roles in grape and attract more and more attentions due to their health benefits (Anastasiadi et al, 2010; Kim et al, 2013; Zhang et al, 2013). During grape berry development, the detected flavonoids presented two distinct changing patterns (Figure 2E).…”
Section: Resultsmentioning
confidence: 99%
“…Grape berries are consumed either as fresh fruit or processed to raisins, juice and wine. Besides its enormous economical and nutritional values, grapes and grape products possess a wide variety of health benefits, such as antioxidation (Sánchez-Moreno et al, 1999; Doshi et al, 2006; Sánchez-Alonso et al, 2007; Sáyago-Ayerdi et al, 2009; Anastasiadi et al, 2010), cardiovascular protection (Tebib et al, 1994; Adisakwattana et al, 2010; Razavi et al, 2013), neuroprotection (Feng et al, 2007), anti-obesity (Kim et al, 2013; Zhang et al, 2013), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this model has been used in a number of studies for the research of DN. [34][35][36] In this study, elevated levels of albuminuria and exacerbated histological alterations indicate damage in kidneys of diabetic db/db mice. Interestingly, UDCA or 4-PBA treatment could restore renal dysfunction and mesangial expansion in db/db mice, suggesting that both treatments effectively prevented the progression of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive expansion of the mesangial matrix is a key histological appearance of DN. 34 The db/db murine model of type 2 diabetes could develop renal dysfunction closely similar to that of humans. Thus, this model has been used in a number of studies for the research of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies (29)(30)(31)(32)(33)(34) have shown that clinical and experimental diabetes are associated with increased formation of free radicals and with decreases in antioxidant potential. In the present study, plasma XO activity significantly increased in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%